Menstrual Dysfunction in Women With Schizophrenia During Risperidone Maintenance Treatment. Issue 2 (March 2021) - Bo, Qijing; Xing, Xiaomeng; Li, Tian; Mao, Zhen; Zhou, Fuchun; Wang, Chuanyue
Abstract: Background: A percentage of women patients with schizophrenia may suffer from menstrual dysfunction associated with antipsychotic medication. This study evaluated menstrual dysfunction in women with schizophrenia given maintenance risperidone, and investigated the association between menstrual dysfunction and the duration and dose of risperidone and clinical symptoms. Methods: The data of 161 women were obtained from the Risperidone Maintenance Treatment in Schizophrenia study, including patients' characteristics, menstrual conditions, and duration and dosage of risperidone. Qualitative data regarding menstrual health were evaluated at baseline (clinical stabilization after 4–8 weeks maintenance treatment with a standard risperidone dose 4–8 mg/d) and follow-up interviews up to 52 weeks. Results: At baseline, 73.2% (119/161) of the patients were eumenorrheic; specific rates of menstrual dysfunction were 14.3% (23/161) irregular menstruation, 6.8% (11/161) oligomenorrhea, and 5.0% (8/161) amenorrhea. At the end of follow-up, 16.0% (19/119) of those with eumenorrhea at baseline reported menstrual dysfunction. During the entire risperidone maintenance treatment, 37.9% (61/161) experienced menstrual dysfunction. The range of onset time from the beginning of risperidone treatment to menstrual dysfunction was 64 to 243 days. Risperidone dose was positively associated with menstrual dysfunction ( r = 0.187, P = 0.046). The total Positive and Negative Syndrome Scale score was significantly associated with menstrual dysfunction ( r = 0.274, P = 0.001). Conclusions: Attention should be given to menstrual dysfunction of women with schizophrenia that is an adverse effect of risperidone maintenance treatment. Menstrual dysfunction may occur early or late during maintenance treatment, partly depending on the dose. ClinicalTrials.gov identifier : NCT00848432